PENGEMBANGAN BAHAN AJAR KOMIK BERBASIS CERITA RAKYAT MENGGUNAKAN APLIKASI CANVA DENGAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SD - Ibnu Salimi; Abdul Muktadir; Agus Susanta (UNIB Press, 2023)
This study aims to develop folklore-based comics teaching materials using the Canva application with the discovery learning model to improve Indonesian language learning outcomes for fourth grade elementary school students. The type of research in this study is the development or Research and Development of the ADDIE model. The research subjects were teachers and fourth grade students at SDN 05 Muara Beliti Plus. The results of this study indicate that 1. The products carried out in the development of teaching materials are as follows: (a) preparing teaching materials, (b) format selection, (c) initial design. 2. Material feasibility, namely the results of validation on the material aspect, obtained an average score 0.93 (Valid), Language feasibility, namely the results of validation on the aspect of language, obtained an average score 0.91 (Very Valid), Feasibility of presentation and Graphically, the validation results obtained an average score of 0.94 (Very Valid). Based on the results of the validation of the three aspects, it can be concluded that the product is suitable for use. 3. Folklore-based comics teaching materials using the Canva application with the discovery learning model are considered effective in improving student learning outcomes in learning Indonesian.